Fractures of modernity. Notes for a policy of detachment with Fanon and Césaire - De Oto, Alejandro (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2015)
The paper discusses the foundational value of politics in Frantz Fanon and Aimé Césaire. The main hypothesis is that their writings produced three concurrent phenomena to perform the critic of colonialism: the colonized agency, and its process of de-subjectivation, delimitation of the colonial body as an absence in very specific orders of discourse and the absence of the human as a sign of singularity.